Comparative Study: Implementation of E-Government in Realizing Improved Public Services in Indonesia and Thailand - I. R. Rantung, Margareth; Anantanathorn, Anurat; Polii, Einjelheart (Iapa Proceedings Conference, 2025)
This study discusses a comparison of the implementation of e-government in Thailand and Indonesia. The purpose of this paper is to describe the implementation of e-government in both Thailand and Indonesia, as well as to compare its implementation and the impact on public services in both countries. This research uses a literature study method, which does not require fieldwork or meeting with respondents. The preparation for this research is similar to other types of research, but the sources and data collection methods involve gathering data from literature, reading, taking notes, and processing research materials. It is hoped that the results of this study can provide recommendations for the governments of both countries to further improve public services to the community.